Oil price shocks, protest, and the shadow economy: Is there a mitigation effect? - Phoebe W. Ishak; Mohammad Reza Farzanegan (Economics & Politics, 2021)
In this study, we look at how oil price shocks affect the incidence of protests in a country and how the size of a country's shadow economy influences this relationship. Using panel data from 144 countries, from the period of 1991–2015, we find evidence that negative oil price shocks significantly increase protests in countries with small shadow economies. The effect dissipates as the size of the shadow economy increases and eventually vanishes in countries with a shadow economy representing more than 35% of gross domestic product. Our analysis departs from existing literature by emphasizing the moderating role of a shadow economy on the effects of negative oil shocks on the incidence of protests in oil-dependent economies. The results are robust to various specifications and their broader implications are discussed.
Keywords: 330; conflict; oil price shocks; protest; resource curse; shadow economy